Comparative genomic insights into adaptation, selection signatures, and population dynamics in indigenous Indian sheep and foreign breeds - Malarmathi Muthusamy; Oludayo Michael Akinsola; Oludayo Michael Akinsola; Pritam Pal; Chitra Ramasamy; Saravanan Ramasamy; Abdulraheem Arome Musa; Aranganoor Kannan Thiruvenkadan (Frontiers in Genetics)
BackgroundIndia’s indigenous sheep breeds have evolved under extreme and diverse agro‐ecological pressures, yet the genomic basis of their resilience and local adaptation remains poorly understood.MethodThis study combines genomic inbreeding estimates, runs of homozygosity (ROH), population structure analyses, and composite selection scans to investigate three native Indian breeds—Changthangi, Deccani, and Garole—within a panel of nine breeds that also includes populations from Africa (Ethiopian Menz), East and South Asia (Tibetan, Chinese Merino, Bangladesh Garole, Bangladesh East), and Europe (Suffolk).ResultsROH and heterozygosity estimates revealed strong contrasts: Bangladesh East sheep exhibited high genomic inbreeding (FROH≈14.4%) and low observed heterozygosity (∼30.6%), whereas Deccani sheep showed low inbreeding (FROH≈1.1%) and high observed heterozygosity (∼35.6%), consistent with broader gene flow and larger flock sizes. Changthangi and Garole showed moderate inbreeding and distinct ROH length profiles. Population structure analyses confirmed ecological clustering and gene flow shaped by geography and husbandry practices: high‐altitude breeds clustered together, while directional migration edges traced admixture from European Suffolk into Changthangi and from Chinese Merino into Ethiopian Menz. Historical effective population sizes showed sharp declines in most breeds, especially those under recent selection. Selection scans identified 118 significant genomic regions across breeds. In Changthangi, key pathways included purinergic signaling, thyrotropin-releasing hormone, and autophagy—consistent with cold and hypoxia adaptation. Deccani showed enrichment for immune adhesion and epidermal regeneration, reflecting parasite resistance and heat stress. Garole displayed signals for gap-junction communication and skeletal development, aligned with high fertility and compact stature.ConclusionThese findings reveal ecotype‐pecific adaptive nature shaped by polygenic selection, gene flow, and demography, offering actionable insights for sustainable smallholder breeding strategies.